TEACHER’S ROLE IN USING INFORMATION TECHNOLOGIES IN EDUCATIONAL PROCESSES - Yuldashov Barhayotjon Toshpulatovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the role of the teacher in the use of information technologies in educational processes and the need for future teachers to keep up with the times.